« Le corps relève de l’ordre social ». Une économie politique de la mise au service des corps dans la sociologie de Nicole Laurin - Jean-Charles St-Louis (Revue Interventions Économiques)
The work of the late sociologist Nicole Laurin paints a picture of the various forms appropriation and domination take in Quebec society – from the rise of neonationalism and the decline of hospital nuns to the erosion of intermediate social institutions. This article aims to provide an outline of the political economy that emerges from this work. It is articulated around two successive portraits. The first one presents a Marxian and anarchist analysis of nationalism and the state. It highlights their central role in implementing and legitimizing the relations of domination produced by capitalism and patriarchy. The second portrait is a radical political economy of the body and its social uses. It inscribes social relations on the horizon of “self-sacrifice”, i.e., “a socio-historical mode by which bodies are to be used and worn”, regulating at various scales their insertion in the processes of (re)production of the society.